THE PHYSICAL ACTIVITY AND THE QUALITY OF LIFE OF SENIOR BELONGING TO TWO GROUPS OF ACQUAITANCE IN BELO HORIZONTE (Fiep Bulletin - online, 2014)
In this work, we analyzed aspects related to the quality of life and the components of physical aptitude that intervene with the health of the elderly. Three tests of functional capacity of the battery of tests from Andreotti e Okuma (1999) were made and the questionnaire WHOQOL bref was given to evaluate the quality of life in four domains: physical, psychological, social and environmental relations. 36 people, all female and physically independent, composed the sample. The subjects belonged to two groups of acquaintance , one in the metropolitan region of Belo Horizonte's capital and the other called “active life“, a social program from the town hall of Belo Horizonte. The results found reveal that significant improvement happened in the execution of the day-to-day activities (DDAs) after the regular practice of regular physical activity for a period of 4 months, leading to a better quality of life to the participants. Therefore, we concluded that physical activity is fundamental to the elderly keep its physical independence and a better quality of life.
Keywords: Senior; Quality of life; Coexistence Groups